Missing Uniform Costs Classification for Alzheimer's Disease Treatment and Care - Maresova, Petra; Kuca, Kamil (Current Alzheimer Research, 2018)
Background: The importance of the issue of the economic burden of treatment and care for people with dementia is crucial in the developed countries. The European Union and other developed countries are trying to improve the course of aging population which leads to rising costs. Their uniform registration is also one of the objectives of the developed countries' strategic plans to fight dementia. The individual steps of the plans in practical terms so far are mainly directed to the early diagnosis of diseases, records of the associated data are so far in the background. Aim: The aim of this paper is to specify a set of costs that should be constantly monitored at the national level within dementia. Methods: The main method is a literature review focused on Alzheimer's disease. The searched keywords were
Keywords: direct costs